(untitled) - Wells, H. G. (Hong Kong, 1972)
The Oxford Progressive English readers series provides a wide range of reading for loaners of English. It incudes classics, the favourite stories of young readers, and also the modern fiction.Grade at 1400-2100-3100 and 3700 word level.
Keywords: English language,Ngôn ngữ tiếng Anh; Reading,Đọc